KINERJA BADAN NARKOTIKA NASIONAL KOTA PONTIANAK DALAM MENCEGAH PENYEBARAN NARKOBA PADA KALANGAN REMAJA KOTA PONTIANAK - Alim Rahman Hakim E.01108095 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this article is the National Narcotics Agency Performance Pontianak Drugs in Preventing Spread The background of this research is still many drug abuse in teenagers. This researcher uses descriptive qualitative research. These results indicate productivity Pontianak City National Narcotics Agency was deficient in providing outreach programs about the effects, prevention, and the level of drug abuse in the youth level. Less melting the National Narcotics Agency Pontianak in the plan-making program with community outreach programs. This is because people are still not satisfied with the services provided BNN Pontianak. Not maximal Pontianak City National Narcotics Agency in response to complaints, suggestions and aspirations of the people gave. With the National Narcotics Agency Pontianak, not to minimize abuse addictive substances among adolescents Pontianak.Keywords: BNN performance of Pontianak City, drug abuse.